1997
DOI: 10.1007/bf02785388
|View full text |Cite
|
Sign up to set email alerts
|

Mercury from maternal “silver” tooth fillings in sheep and human breast milk

Abstract: Neonatal uptake of mercury (Hg) from milk was examined in a pregnant sheep model, where radioactive mercury (Hg203)/silver tooth fillings (amalgam) were newly placed. A crossover experimental design was used in which lactating ewes nursed foster lambs. In a parallel study, the relationship between dental history and breast milk concentration of Hg was also examined in 33 lactating women. Results from the animal studies showed that, during pregnancy, a primary fetal site of amalgam Hg concentration is the liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 9 publications
1
19
1
Order By: Relevance
“…Levels difference depending on sampling place, time, and exposure levels of the mothers. Our result of mercury milk levels are compared with data from the literature; the mercury levels found in breast milk in the present study are quite high, and higher than those found in Germany by (Drasch et al Drasch et al (1998)), Vimy et al (1997) and Klemann et al (1990); Table 2.…”
Section: Resultscontrasting
confidence: 48%
See 3 more Smart Citations
“…Levels difference depending on sampling place, time, and exposure levels of the mothers. Our result of mercury milk levels are compared with data from the literature; the mercury levels found in breast milk in the present study are quite high, and higher than those found in Germany by (Drasch et al Drasch et al (1998)), Vimy et al (1997) and Klemann et al (1990); Table 2.…”
Section: Resultscontrasting
confidence: 48%
“…These results were in a great extent compatible with other studies. Vimy et al (1997), Oskarsson et al (1996), Drasch et al (1998), Klemann et al (1990), Langworth et al (1991) and Ursinyova and Masanova (2005) detected significant differences in mothers milk mercury levels between mothers with and without amalgam-filled teeth.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The slow release of Hg from amalgams is known to select for Hg-resistant bacteria in the gut [59]. Ag is also released [42] and Ag-resistant oral bacteria were recently reported [14].…”
Section: History Of Biocidal Uses Of Silver Products In Clinical Applmentioning
confidence: 98%